(untitled) (Research, Society and Development, 2021)
In mid-March 2020, the activities of an extension project on wounds were carried out in an outpatient clinic of a university hospital in the capital of Piauí. However, due to the pandemic and its worldwide repercussion, such activities were suspended and adapted to the remote modality. Therefore, the objective was to report the experience of nursing students in the area of stomatherapy during the COVID-19 pandemic, highlighting the use of remote means to carry out extension actions. This is an experience report of nursing extensionists in the area of ​​stomatherapy, during the year 2020. Initially, digital banners and videos addressing coronavirus prevention were produced, which were disseminated through social media. Then, two booklets were created on how to prevent Pressure Injury and a folder on wound care at home. Also, an online class was promoted in order to guide professionals and students on the production of educational videos. The experience made it possible to broaden the perspective of students and professionals on remote means of informing the population and understanding the benefits of such resources in the management of health crises such as the one caused by COVID-19.